2001
DOI: 10.1128/cdli.8.4.718-723.2001
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment Follow-Up of Helicobacter pylori Infection Using a Stool Antigen Immunoassay

Abstract: The Helicobacter pylori stool antigen enzyme immunoassay (HpSA) was evaluated during posttreatment follow-up of patients in a country with a very high prevalence of H. pylori infection. From among 273 dyspeptic individuals (18 to 55 years) initially recruited from a shantytown in Lima, Peru, 238 participants who met the inclusion criteria and were suspected to be H. pylori positive based on 14 C urea breath test (UBT) results underwent endoscopy. Participants with endoscopy-proven infections received standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…A comparative study of these two methods indicated a 75% agreement of results. These data are consistent with those obtained by other authors (Roth et al. 2001; Wisniewska et al.…”
Section: Discussionsupporting
confidence: 94%
“…A comparative study of these two methods indicated a 75% agreement of results. These data are consistent with those obtained by other authors (Roth et al. 2001; Wisniewska et al.…”
Section: Discussionsupporting
confidence: 94%
“…The efficacy was not affected by the consumption of coffee or Chinese tea, or cigarette smoking. In agreement with other published studies, the HpSA test is a good alternative for the testing of H. pylori status in both non‐treated 3–7 and treated 5 , 7 , 12–15 patients.…”
Section: Discussionsupporting
confidence: 91%
“…Eighty‐nine studies, including 10,858 patients, fulfilled the inclusion criteria and evaluated the accuracy of the stool antigen test for the diagnosis of H. pylori in untreated patients (Table 1) [14–95]. Some of the studies reviewed included, in the same protocol, patients before and after therapy, without separating them depending on the time at which the H. pylori stool antigen test was performed, thus preventing us from calculating the true diagnostic accuracy in each circumstance [96–100].…”
Section: Resultsmentioning
confidence: 99%